Measuring Arabic Reading Skills of New Students in Islamic Senior High School at Pandemic Era - Istiqomah, Himatul (Nurul Jadid University, 2024)
This study investigates the post-pandemic Arabic reading proficiency of newly enrolled students at an Islamic senior high school, with a focus on identifying disparities in comprehension and decoding skills. Using a quantitative descriptive design, the research assessed 118 students through a structured performance test measuring four core components: letter recognition, vocabulary understanding, sentence comprehension, and short discourse interpretation. Data were supported by observation logs and documentation. Results show that while 84% of students demonstrated strong decoding abilities, only 38% could comprehend simple sentences, and less than 25% could understand short texts. The analysis further revealed a stark proficiency gap between students from Madrasah Aliyah (MA) and those from senior high schools (SMA), indicating that prior exposure and institutional background significantly affect reading competence. This study contributes to Arabic education research by providing diagnostic insight into the cognitive impact of pandemic-era learning and the need for targeted remediation. However, its limitation lies in the single-site context and lack of longitudinal tracking, suggesting a need for future multi-phase studies to explore intervention outcomes.